FACTORS FOR STRENGTHENING THE FEELINGS OF UNSOCIALIZED YOUNG PEOPLE (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Unorganized youth, in a broad sense, can be understood as part of them who are disconnected from one or another field of education, do not actively participate in labor unions, state institutions and public organizations